Demand Uncertainty and the Optimal Number of Export Destinations - Eliav Danziger; Leif Danziger (Institute of Labor Economics (IZA), 2025)
We study how demand uncertainty affects risk-neutral firms' number of export destinations when uncertainty is resolved after firms choose their export destinations and output. We show that firms' ability to allocate their output across destinations in response to destination-specific shock realizations provides even risk-neutral firms an incentive to export. Without appealing to firm-country heterogeneity or increasing marginal cost, our framework can explain why firms export to some but not all ex-ante indistinguishable destinations. We also show how, for a given firm productivity, the optimal number of export destinations depends on the correlation of shocks across the home and foreign countries.
Keywords: F12; F61; 330; international trade; demand uncertainty; risk-neutral firms; optimal number of export destinations